EFEKTIVITAS TERAPI MUSIK KLASIK MOZART TERHADAP PENURUNAN SKOR HALUSINASI PENDENGARAN PADA PASIEN SKIZOFRENIA - Rosiana, Rosiana; Jumaini, Jumaini; N, Yesi Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Music therapy can be used as a therapy for psychiatric disorders, medical problems and communication disorders. Oneof the therapies that can be utilized is the Mozart classical music therapy. This study aimed to determine theeffectiveness of Mozart classical music therapy against hallucinations in schizophrenic patients. This research used aquasi-experimental design in the form of nonequivalent control group design. The sample was 30 respondents dividedinto 15 experimental group and 15 control group. Samples were taken based on inclusion criteria using purposivesampling technique. The instrument used was the Auditory Hallucination Rating Scale (AHRC) questionnaire. Thestudy was analyzed by univariate analysis to know the frequency distribution and bivariate analysis using Wilcoxon andMann-Whitney. The results showed the mean of posttest hallucination score in the experimental group was 13.00 and inthe control group was 27.00. The study found that there was a significant difference in hallucination scores after givingMozart classical music therapy between the experimental group and the control group with p-value 0.000 <(0.05). So itcan be concluded that the therapy of Mozart classical music is effective on the reduction of hallucinations inschizophrenic patients. This study recommends the effectiveness of other therapies that can be associated withhallucinatory patients.Keywords:Hallucinations score, Mozart classical music therapy, schizophrenia